Teaching a foreign language through the multiple intelligences. An attempt for improving the English language level in sixth grade students from Colegio Distrital Gustavo Restrepo (2016)
This research aims at demonstrating the positive impact of implementing creative teaching strategies in class learning English as a foreign language. To carry out this research a sampled sixth grade group from the Colegio Distrital Gustavo Restrepo located in the Rafael Uribe locality in Bogotá, this group consisted of 29 children aged between 12 and 14 years.